The Green and Inclusive School: Bridging Environmental Education and Social Justice through Strategic Principal Leadership - Mamik Ekawati; Gufron Abdullah; Lilik Ariyanto (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyse the strategic role of school principals in planning, implementing, and evaluating inclusive education within the Adiwiyata schools framework (environmentally conscious schools). To achieve this, a qualitative case study approach was used, employing data collection techniques such as in-depth interviews, direct observation, and documentation, followed by data analysis using the Miles, Huberman, and Saldana model. The results revealed that the principals act as transformative leaders who integrate inclusive values into the school's vision, motivate teaching staff to implement adaptive curriculum practices, and ensure the availability of disability-friendly facilities. Furthermore, the evaluation process involves continuous monitoring to synchronise environmental programs with inclusive policies, thereby creating a synergistic educational ecosystem. The primary objective and contribution of this study are to provide a comprehensive management model that bridges the gap between environmental education and inclusivity. By offering practical insights on how leadership can foster an environment that is